APLIKASI GAME EDUKASI UNTUK MERANGSANG OTAK ANAK-ANAK DALAM MENGENAL DAN BELAJAR PENDIDIKAN AGAMA ISLAM MENGGUNAKAN CONSTRUCT 2 BERBASIS ANDROID - Erma Sova (Jurnal Teknik dan Science, 2023)
Learning is quickly developed by several experts, both from professionals in this case are observers of children, namely those who work as psychologists supported by hardware and software makers from the computer field. This aims to stimulate children in accepting and recognizing learning methods that are fun and not boring, namely learning to play, especially for children with an age interval of 5-10 years. Because childhood is still a difficult playing period if invited to learn seriously. The method used in this study is using the MDLC (Multimedia Development Life Cycle) method with stages such as concept, design, material collection, manufacturing, testing and deployment. Making Islamic Religious Education Educational Game Applications using Construct 2 is able to help foster honest character, responsibility, respect for others and manners. Game application results provide fun entertainment and education for children aged 5-10 years, especially with the theme or educational background of the Islamic religion. This way of learning in the form of adaptation of learning while playing is very attractive to children.